Simultaneous Extraction of Bone Marrow RNA and DNA from Patients with Hematologic Diseases Using a Combined Magnetic Bead Method within 1 Hour - Mu, Huijun; Zou, Jian; Zhang, Haiping (The journal of applied laboratory medicine, 2024)
TRIzolTM is widely used for RNA and DNA extraction. However, this method is laborious and time-consuming. The objective of this study was to validate a time-effective and labor-saving protocol. The TRIzol method was used to separate the aqueous phase, protein, and phenol layer of bone marrow samples from 12 patients with hematological diseases. Subsequently, RNA and DNA were extracted from the aqueous layer containing RNA and phenol layer containing DNA, respectively, using magnetic bead extraction kits. The quantity and purity of extracted RNA and DNA were examined using a NanoDrop spectrophotometer. Quantitative fluorescence PCR amplification of the ABL1 gene was performed to verify the effectiveness of the extracted RNA and DNA for downstream experiments. RNA and DNA from another 16 bone marrow samples were extracted to compare the performance of the two methods. Co-extraction of RNA and DNA was completed within 1 h. The data showed that RNA and DNA yield ranged from 13.1 to 204.5 ng/µL and 33.1 to 228.8 ng/µL, respectively. The A260/A280 ratios of RNA and DNA samples ranged from 1.82 to 2.01 and 1.73 to 1.91, respectively. RNA and DNA extracted using this scheme exhibited ideal performance in quantitative fluorescence PCR. The present protocol showed better quality and effectiveness in extracting RNA and DNA compared to the TRIzol method. This protocol for RNA and DNA co-extraction is fast, labor-saving, and high throughput. It can be adopted for routine molecular biology analyses, particularly for non-reproducible specimens.